Notes on the foraging behaviour of Magellanic Flightless Steamer Ducks and Flying Steamer Ducks - Ryan, P G; Bosman, A L; Hockey, P A R (Wildfowl, 1988)
Marine foraging behaviour of Magellanic Flightless Steamer Ducks Tachyeres pteneres and Flying Steamer Ducks T. patachonicus is described from two localities in southern Chile. Paired birds feed together, diving synchronously. Maximum dive-times of 58 s in pteneres and 45 s in patachonicus were recorded. Males dived for longer than females, presumably as a result of dietary differences.